Analysis of Curcumin Contents in Curcuma xanthorrhiza using FTIR Spectroscopy and HPLC-UV in Combination with Multivariate Calibration - Kusumadewi, Awal P.; Mujahid, Rohmat; Martien, Ronny; Purwanto, Purwanto; Styawan, Anita A.; Irnawati, Irnawati; Rohman, Abdul (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Curcuma xanthorrhiza Roxb. or Java Turmeric with the local name of Temulawak is one of herbal medicines used in Indonesia. This plant is believed to prevent some degenerative diseases due to its active compounds, especially curcumin (CUR) contained in Java Turmeric. Therefore, analysis of active components including CUR is very urgent. This study highlighted the development of FTIR spectroscopy coupled with PLSR for the determination of CUR in Java Turmeric powders. The levels of CUR in Java Turmeric powders were determined using HPLC with UV detectors, and the obtained results were used as actual values to be predicted using FTIR spectroscopy-multivariate calibrations. The results revealed that the levels of CUR ranged from 0.6741 ± 0.0705% (g/100 samples) to 2.1062 ± 0.0095%. PLSR modeling for the relationship between the actual value of CUR as determined using HPLC and calculated values as predicted using FTIR spectroscopy provide the value of R2 of 0.9990 with RMSEC of 0.0028. The developed method offers reliable results providing a green analytical method due to the use of minimum solvent and reagent and does not involve extensive sample preparation.